Analytical model of signal generation for radio over fiber systems (2014)
This paper presents an analytical model that describes the elements involved in the signal generation feasible to be used in radio over fiber systems for the transport of information. In these systems, the radio frequency carriers are conveyed as optical subcarriers over an optical fiber link in a point-to-point or point-to-multipoint connectivity paradigm. The model is based on the definition of both the electrical field and power at the output of the optical modulator for baseband and radiofrequency modulated signals. By modeling the electrical field, it was found a trade-off between the modulation depths of both signals; as well as the their optimum value in order to assure a good signal quality in reception.